AN EXISTENCE AND UNIQUENESS OF THE WEAK SOLUTION OF THE DIRICHLET PROBLEM WITH THE DATA IN MORREY SPACES - Nicky Kurnia Tumalun (Barekeng)
Let n-2<λ<n , f be a function in Morrey spaces L^{1,λ}(Ω) , and the equation